Host genetic heterozygosity and age are important determinants of porcine circovirus type 2 disease prevalence in European wild boar - Goedbloed, D. J.; van Hooft, P.; Megens, H.-J.; Bosch, T.; Lutz, W.; van Wieren, S. E.; Ydenberg, R. C.; Prins, H. H. T. (European journal of wildlife research, 2014)
Emerging and zoonotic diseases are important challenges for veterinary and public health. It is therefore a key issue to assess the relative importance of various factors for disease dynamics and to understand the mechanisms behind these factors and interactions. Here, we evaluate the influence of a number of demographic and genetic factors on porcine circovirus type 2 (PCV2) antibody prevalence in the European wild boar ( Sus scrofa ). We measured PCV2 blood serum antibody levels of 462 randomly sampled wild boars from a cross-border area in the Netherlands and western parts of Germany in a 3-year period. These samples were also genotyped using a randomly selected genome-wide 351 SNP assay. Generalized linear mixed model analysis shows that wild boar PCV2 antibody status is determined by age and genetic heterozygosity, with an idiosyncratic influence of the year of sampling. In contrast, sex, population membership and domestic hybrid status did not significantly affect PCV2 antibody status. The observed positive relationship between PCV2 antibody status and age is most likely caused by cumulative exposure and PCV2-typical intracellular hiding behaviour. The observed positive relationship between wild boar genetic heterozygosity and PCV2 antibody status could be attributed to disappearance of relatively inbred (low-heterozygosity) individuals. This finding suggests that PCV2 can act as a selective force in wild boar populations and that disease mortality can be mediated by host heterozygosity.